2020
DOI: 10.1093/rheumatology/keaa783
|View full text |Cite
|
Sign up to set email alerts
|

Positive disease-specific autoantibodies have limited clinical significance in diagnosing IgG4-related disease in daily clinical practice

Abstract: Objectives The 2019 ACR/EULAR classification criteria for IgG4-related disease (IgG4-RD) have exclusion criteria including positive disease-specific autoantibodies, and these have been documented to have a high specificity. This study aimed to further validate these criteria as well as identify characteristics of patients showing false-negative results. Methods We retrospectively analysed 162 IgG4-RD patients and 130 mimicker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, although biopsies are essential in many settings to establish the diagnosis of IgG4‐RD and exclude mimickers, the new classification criteria 6 showed that an important strength of this criteria set is that a patient may be classified accurately as having IgG4‐RD in many cases on the basis of clinical, serological, and radiological findings even in the absence of a biopsy. Mizushima et al's research 7 also showed that the above classification criteria had a sensitivity of 72.8% and specificity of 100%, and even when the exclusion and inclusion criteria related to biopsy results were removed from the classification algorithm, the sensitivity drastically decreased to 42.6%, while the specificity was still maintained (100%).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, although biopsies are essential in many settings to establish the diagnosis of IgG4‐RD and exclude mimickers, the new classification criteria 6 showed that an important strength of this criteria set is that a patient may be classified accurately as having IgG4‐RD in many cases on the basis of clinical, serological, and radiological findings even in the absence of a biopsy. Mizushima et al's research 7 also showed that the above classification criteria had a sensitivity of 72.8% and specificity of 100%, and even when the exclusion and inclusion criteria related to biopsy results were removed from the classification algorithm, the sensitivity drastically decreased to 42.6%, while the specificity was still maintained (100%).…”
Section: Discussionmentioning
confidence: 98%
“…The literature showed that although the serum IgG4 levels could elevate in non-IgG4-RD patients, the elevated levels were slight. 7,10 Hypercalcemia occurring in patients with IgG4-RD is not common. A literature review showed that only 5 definitely [11][12][13][14][15] (including 1 conference abstract 15 ) and 2 possible (not biopsied) IgG4-RD 16,17 associated hypercalcemia had been reported (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in Japan reported that MPO-ANCA and PR3-ANCA seropositivity for GPA was 54.6% and 45.5%, respectively ( 12 ). A recent report concluded that the presence of ANCA does not influence the pathomechanisms of IgG4-related diseases ( 13 ). However, an overlap of ANCA-associated vasculitis and IgG4-related disease has been reported ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…They had elevated serum IgG4 levels (>135 mg/dl for most patients) and positive ANCA. Although AAV is an important differential diagnosis of IgG4-RD in both the 2019 ACR/EULAR classification criteria ( 19 ) and CDC for IgG4-RD, a recent report concluded that the presence of ANCA might not influence the pathomechanisms of IgG4-RD ( 20 ). Furthermore, an overlap of AAV and IgG4-RD has been reported in some clinical patterns, such as tubulointerstitial nephritis, periaortitis, and prevertebral fibrosis ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%